Neogene seismites and seismic volcanic rocks in the Linqu area, Shandong Province, E China - Tian, H.S.; Zhang, B.H.; Zhang, S.H.; Lü, M.Y. (Geologos, 2014)
The Yishu Fault Zone runs through the centre of Shandong Province (E China); it is a deep-seated large fault system that still is active. Two volcanic faulted basins (the Shanwang and Linqu Basins) in the Linqu area, west of the fault zone, are exposed to rifting, which process is accompanied by a series of tectonic and volcanic earthquakes with a magnitude of 5-8. Lacustrine sediments in the basins were affected by these earthquakes so that seismites with a variety of soft-sediment deformation structures originated. The seismites form part of the Shanwang Formation of the Linqu Group. Semi-consolidated fluvial conglomerates became deformed in a brittle way; these seismites are present at the base of the Yaoshan Formation. Intense earthquakes triggered by volcanic activity left their traces in the form of seismic volcanic rocks associated with liquefied-sand veins in the basalt/sand intercalations at the base of the Yaoshan Formation. These palaeo-earthquake records are dated around 14-10 Ma; they are responses to the intense tectonic extension and the basin rifting in this area and even the activity of the Yishu Fault Zone in the Himalayan tectonic cycle.